Evolution of functional size measures through ICONIX process phases. Issue 5 (11th December 2019) - Liu, Geng; Lavazza, Luigi; Tosi, Davide
Abstract: Functional size measures are used in several software development processes, because they can be applied as soon as the functional user requirements of a software application have been specified. Quite often, functional user requirements are used as the main input of effort and cost estimation. Since effort and cost estimates are fundamental for decision making, project managers would like to get reasonably accurate estimates even before user requirements have been specified completely and at the proper level of detail. To this end, early size estimation methods have been proposed. In this paper, we consider a specific situation; namely, we consider processes in which the requirements elicitation and modeling phases are carried out according to the ICONIX process. The ICONIX process involves a few stages, each one tackling an aspect of requirements and delivering a specific artifact, in the form of a UML model. We explore the possibility of deriving from ICONIX artifacts the information needed to estimate the final size of the application. To this end, we analyzed the requirements of 21 software applications and derived statistical models that correlate the information extracted from ICONIX artifacts to the size, expressed in function points, of the application. The analysis of the achieved estimates shows that the approach is viable, in that it provides early estimates with good accuracy. Abstract : Estimates of the functional size of software applications to be built are often needed even before requirements elicitation is complete. During the ICONIX elicitation process, progressively more complete and detailed models of requirements are released. On the basis of that information, progressively more accurate size estimates can be derived.